2018
DOI: 10.1155/2018/6390706
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reformation of the Anterior Chamber by Air or by a Balanced Salt Solution (BSS) on Corneal Endothelium after Phacoemulsification: A Comparative Study

Abstract: Aim To study the effect of reformation of the anterior chamber by air or by a balanced salt solution, after smooth phacoemulsification on the corneal endothelial count and morphology. Methods A prospective interventional nonrandomized comparative study included 500 eyes of 500 patients with age range between 50 and 60 years, prepared for cataract surgery and presented to the Ophthalmology department of Sohag University Hospital in the period from October 2016 to May 2017. Corneal endothelial morphology and cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
(17 reference statements)
1
5
0
Order By: Relevance
“…The result goes with Alsmman A et al study 29 , which included 500 eyes of 500 patients with age range between 50 and 60 years, the authors compared the effect of air and BSS injected into the anterior chamber post smooth phacoemulsification surgery on corneal endothelial loss. They reported the reformation of the anterior chamber by air injection has no toxic effect on the corneal endothelium.…”
Section: Discussionsupporting
confidence: 55%
“…The result goes with Alsmman A et al study 29 , which included 500 eyes of 500 patients with age range between 50 and 60 years, the authors compared the effect of air and BSS injected into the anterior chamber post smooth phacoemulsification surgery on corneal endothelial loss. They reported the reformation of the anterior chamber by air injection has no toxic effect on the corneal endothelium.…”
Section: Discussionsupporting
confidence: 55%
“…However, in over 1000 cases of phacoemulsi cation cataract surgery with IABT that had been reported, including 201 cases in this study, no endophthalmitis was noted. 19,24,25 In our secondary analysis, postoperative CCT was more thickened in the non-IABT group. (11.2µm vs. 5µm; P = 0.034) Subclinical corneal edema caused by stromal hydration, which could not be observed by slit lamp biomicroscope, can be detected under specular microscope.…”
Section: Discussionmentioning
confidence: 79%
“…This nding was consistent with that of Alsmman et al, who have conducted a prospective non-randomized study allocating 500 cataract surgeries of 500 patients into IABT and non-IABT groups. 24 However, another prospective non-randomized study with 100 cases reported by Mataftsi et al showed a completely opposite result, that the ECD loss was signi cantly higher in the IABT group. 25 This difference may be caused by the selection bias, that these two studies and ours were all non-randomized.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The endothelial cell density of the two groups was found to be similar preoperatively and at 3 months postoperatively [18]. Likewise, Alsmman et al [19] studied air bubble versus balanced salt solution for anterior chamber reformation at the end of phacoemulsi cation and found similar endothelial cell count-morphology in both groups at 1 and 3-month follow-up visits. In contrast, Mataftsi et al [20] compared intrastromal wound hydration with anterior chamber air tamponade to ensure waterproof closure of corneal incisions at the end of the phacoemulsi cation surgery and reported that air has a detrimental effect on endothelial cell count compared to balanced salt solution.…”
Section: Discussionmentioning
confidence: 83%